Pelatihan Budidaya Ikan Dan Sayur Dalam Ember Untuk Ketahanan Pangan Keluarga - Transna Putra Urip; Sarlota Arrang Ratang (The Community Engagement Journal, 2021)
Living in urban area makes us unable to grow crops or garden because of limited land. Many innovations have been discovered, including: tabulampot, verticulture, hydroponics, and aeroponics. By implementing these innovations ,the problems as above can be solved. This is because these four methods do not require a large area of land, and only take a short time. The purpose of this activity is so that mothers in RT 011 / RW 006 Kotaraja can practice how to cultivate fish and vegetables in buckets for family food security. The results of this training activity include, the achievement of training objectives, the achievement of planned material targets and the ability of participants to understand the material. The participants of this training were 9 mothers around the activity location, due to the Covid-19 pandemic situation. Of the 9 mothers, then they are willing to continue this training information, each mother becomes 2 people.So there are 26 mothers who get this training information. This figure shows that this training/socialization activity can be said to be a target of participants who reach 87% can be said to be successful.